Pengaruh Etos Kerja dan Kedisiplinan terhadap Kinerja Karyawan - Melisa Andriani (Universitas Islam Kadiri, 2018)
This research is quantitative research using two independent variable that is influence of work ethics and discipline, using one dependent variable that is employee performance. The object of research is all employees in PT Tugu Raya. Test t obtained t arithmet variable work ethos first hypothesis which states there is influence work ethos work on employee performance accepted, while variable of discipline second hypothesis which states there is influence of discipline to employee performance accepted. From the research of regression shows that work ethic has regression coefficient of 0.663 and discipline has regression coefficient of 0.206. So every increase in work ethic will add employee performance of 0.663 and discipline of 0.206. From these results the work ethic and discipline have a positive and significant effect on employee performance. Coefficient of determination shows the value of R square is equal to 0.796 or equal to 79.6%, it shows that employee performance in PT Tugu Raya Kediri influenced by work ethic and work discipline of 79.6%, and the remaining 21.4% influenced by factors - internal and external factors not addressed in this study as well as motivation, wage benefits, incentives, safety etc.